Genes in the field: On-farm conservation of crop diversity - Brush, Stephen B. (2000)
A primary goal of agricultural research is to develop technology that will enable the world's farmers to produce enough food in a manner that is sustainable and economically viable. This book comprises a collection of papers focusing on agricultural conservation and diversity issues throughout the world. Genetic diversity is important to individual farmers and farming communities and to the agricultural community in general. Recently regional and local farm seed variety has been reduced because of increased population, agricultural science and technology and the integration of the world's many diverse cultures. Papers discuss both in situ and ex situ conservation strategies, and present a number of case studies with an international perspective. Policy and institutional issues are also covered. (Abstract © CAB ABSTRACTS, CAB International)